Quarantine host range and natural history of Gadirtha fusca, a potential biological control agent of Chinese tallowtree (Triadica sebifera) in North America. Issue 11 (18th December 2018) - Wheeler, Gregory S.; Jones, Emily; Dyer, Kirsten; Silverson, Nick; Wright, Susan A.
Abstract: Classical biological control can provide an ecologically sound, cost‐effective, and sustainable management solution to protect diverse habitats. These natural and managed ecosystems are being invaded and transformed by invasive species. Chinese tallowtree, Triadica sebifera (L.) Small (Euphorbiaceae), is one of the most damaging invasive weeds in the southeastern USA, impacting wetlands, forests, and natural areas. A defoliating moth, Gadirtha fusca Pogue (Lepidoptera: Nolidae), was discovered feeding on Chinese tallowtree leaves in the weed's native range and has been tested for its suitability as a biological control agent. Natural history studies of G. fusca indicated that the neonates have five instars and require 15.4 days to reach pupation. Complete development from egg hatch to adult emergence required 25.8 days. No differences were found between males and females in terms of life history and nutritional indices measured. Testing of the host range of G. fusca larvae was conducted with no‐choice, dual‐choice, and multigeneration tests and the results indicated that this species has a very narrow host range. No‐choice experiments indicated that most larvae died in <3 days when fed each of the 78 non‐target taxa; a similar duration as larvae fed only water. Although 81.6% of the neonates fed Chinese tallowtree survived to adult, the only survivors in no‐choice tests were those fed the four non‐target taxa, Euphorbia hypericifolia L., Euphorbia hyssopifolia L., Euphorbia milii Des Moul., or Gymnanthes lucida Sw. where 14.3% or less of the larvae fed and completed development. The results of dual‐choice tests indicated that very little of each of these non‐target taxa was eaten when given a choice with Chinese tallowtree. Furthermore, when neonates were reared for multiple generations on each non‐target taxon, no more than two generations were completed when fed the non‐target G. lucida, whereas the larvae were unable to complete more than one generation when fed the remaining non‐targets. These tests indicate that although a small amount of feeding may occur in no‐choice conditions on four species of non‐targets, the larvae will not be able to maintain a population for more than two generations on any species except the target weed Chinese tallowtree. This species may play an important role and contribute to the integrated control of this invasive weed. Abstract : This research examined the quarantine host range of Gadirtha fusca (Lepidoptera: Nolidae), a potential biological control agent of Chinese tallowtree (Euphorbiaceae). Results indicate that this species has narrow specificity and will be a safe control agent of this invasive weed.